Sestrin2: Its Potential Role and Regulatory Mechanism in Host Immune Response in Diseases - Wang, Li-Xue; Zhu, Xiao-Mei; Yao, Yong-Ming (Frontiers in Immunology, 2019)
Sestrin2 (SESN2), a highly evolutionarily conserved protein, is critically involved in cellular responses to various stresses. SESN2 has a protective effect on physiological and pathological states mainly via regulating oxidative stress, endoplasmic reticulum stress, autophagy, metabolism, and inflammation. In recent years, breakthrough investigations with regard to the regulation and signaling mechanisms of SESN2 have markedly deepened our understanding of its potential role as well as its significance in host response. However, the functions of SESN2 in the immune system and inflammation remain elusive. It has been documented that many immune cells positively express SESN2 and, in turn, SESN2 might modulate cellular activities. This review incorporates recent progress and aims to provide novel insight into the protective role and regulatory pathway of SESN2, which acts as a potential biomarker and therapeutic target in the context of inflammatory-related diseases.